Students’ technological skills and attitudes toward HyFlex learning: the mediating role of online self-regulated learning, blended learning perception, and preferred learning modes - Amiruddin, Amiruddin; Sunardi, Sunardi; Setialaksana, Wirawan (Frontiers in Education, 2024)
Introduction HyFlex learning has been used and researched in colleges in developing countries. The main challenges in HyFlex adaptation in college are technology related variables. However, the investigations about HyFlex and the factors affect it were limited. Methods The current study aims to explore student technological skills effect on their attitudes toward HyFlex learning using 738 Indonesian college students. The mediating role of online self-regulated learning (SRL), perceptions on blended learning, and student’s preferred learning modes were also investigated. The relationship between variables were analyzed using structural equation modelling with partial least square parameter estimations (PLS-SEM). Results Results of structural equation modeling analysis show that student technological skills have significant effect on their attitude toward HyFlex learning. Mediation analysis revealed that student technological skills have indirect significant effect on their attitude toward HyFlex learning, i.e., online self-regulated learning, perceptions on blended learning, and online asynchronous and face to face learning preference partially mediated the effect of student technological skills on their attitude toward HyFlex learning. PLS-SEM conducted also shows that student technological skills have direct effect on their online self-regulated learning and perceptions on blended learning. Online self-regulated learning and perceptions on blended learning were also shown to have direct effect on student’s attitude toward HyFlex learning. Discussion By comprehending the factors that influence student attitudes towards HyFlex learning, educators and policymakers can endeavor to create a more conducive environment that enhances students’ motivation and engagement in this flexible learning approach.